2018
DOI: 10.1007/s00531-018-1655-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural, lithological, and geodynamic controls on geothermal activity in the Menderes geothermal Province (Western Anatolia, Turkey)

Abstract: Western Turkey belongs to the regions with the highest geothermal potential in the world, resulting in significant electricity production from geothermal resources located predominantly in the Menderes Massif. Although geothermal exploitation is increasingly ongoing, geological and physical processes leading to the emplacement of geothermal reservoirs are hitherto poorly understood. Several studies on the Menderes Massif led to different interpretations of structural controls on the location of hot springs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 140 publications
(193 reference statements)
1
16
0
Order By: Relevance
“…The rollback in the Aegean and the steepening of the Cyprus slab started subsequently. Even thermal anomalies in western Anatolia, extending from the upper mantle into the crust, might be generated by the rollback and slab tearing (Roche et al, 2019). Biryol et al (2011) and Portner et al (2018) found evidence for a smaller tear in the Cyprian trench, defining an eastern and a western Cyprian slab and linked the tearing to volcanism in the Central Anatolian Volcanic Province.…”
Section: Tectonic Setting Of the Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rollback in the Aegean and the steepening of the Cyprus slab started subsequently. Even thermal anomalies in western Anatolia, extending from the upper mantle into the crust, might be generated by the rollback and slab tearing (Roche et al, 2019). Biryol et al (2011) and Portner et al (2018) found evidence for a smaller tear in the Cyprian trench, defining an eastern and a western Cyprian slab and linked the tearing to volcanism in the Central Anatolian Volcanic Province.…”
Section: Tectonic Setting Of the Regionmentioning
confidence: 99%
“…The rollback in the Aegean and the steepening of the Cyprus slab started subsequently. Even thermal anomalies in western Anatolia, extending from the upper mantle into the crust, might be generated by the rollback and slab tearing (Roche et al., 2019). Biryol et al.…”
Section: Introductionmentioning
confidence: 99%
“…In the shallow crust (above the brittle-ductile transition), permeability is expected to decrease with increasing lithostatic pressure (e.g., Manning and Ingebritsen, 1999;Saar and Manga, 2004;Achtziger-Zupančič et al, 2017), but this depth dependence may be less effective in highly permeable fault zones, like extensional faults in the Larderello and other geothermal systems (Della Vedova et al, 2008;Scibek, 2020). In the case of a constant-pressure boundary condition at the top surface (a more realistic condition for geological systems than a "no-flow" condition), the fact that permeability decreases with depth has important consequences for convective patterns.…”
Section: Depth-dependent Permeabilitymentioning
confidence: 99%
“…see Roche et al, 2018b]. Slab dynamics controls the bulk of heat source at the base of the crust and therefore explains (i) the different pattern of deformation, asymmetrical in the central and eastern Aegean Sea versus symmetrical in the western Cyclades and in the Menderes Massif, which may be related to the activity of asthenospheric flow underneath , (ii) the retrogression in greenschist-facies or amphibolite-facies conditions within the metamorphic domes in the Aegean domain, (ii) the current localization of geothermal resources in the Menderes Massif [Gessener et al, 2018;Roche et al, 2018c].…”
Section: Cyclades and Menderes Massif) (See The Compilation Ofmentioning
confidence: 99%